2016
DOI: 10.1200/jco.2015.64.3536
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Locoregional Recurrence Rates in Young Patients With Early-Stage Breast Cancer

Abstract: Purpose The aim of this study was to evaluate contemporary rates of local recurrence (LR) and regional recurrence (RR) in young patients with breast cancer in relation to tumor biology as expressed by biomarker subtypes. Patients and Methods Women < 35 years of age who underwent surgery for primary unilateral invasive breast cancer between 2003 and 2008 were selected from the Netherlands Cancer Registry. Patients were categorized according to biomarker subtypes on the basis of hormone receptor (HR) and huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
41
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 36 publications
5
41
3
Order By: Relevance
“…These data compare closely to the Prospective study of Outcomes in Sporadic and Hereditary breast cancer (POSH), where data was collected from 2000 to 2008: 73% of patients < 40 yo received adjuvant chemotherapy, predominately anthracycline based [15]. Also, in a Netherlands cohort, collected between 2003 and 2008, 93% of patients < 35 yo had chemotherapy [29]. The data confirm a practice of widespread use of chemotherapy in young breast cancer patients.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…These data compare closely to the Prospective study of Outcomes in Sporadic and Hereditary breast cancer (POSH), where data was collected from 2000 to 2008: 73% of patients < 40 yo received adjuvant chemotherapy, predominately anthracycline based [15]. Also, in a Netherlands cohort, collected between 2003 and 2008, 93% of patients < 35 yo had chemotherapy [29]. The data confirm a practice of widespread use of chemotherapy in young breast cancer patients.…”
Section: Discussionsupporting
confidence: 66%
“…In the DoD cohort, patients < 40 yo underwent proportionally more mastectomies (69%), with fewer breast conserving surgeries (31%). The mastectomy rate is higher than that reported for patients < 35 yo from the Netherlands, where 45% had breast conserving therapy and 55% mastectomy [29]. Breast conserving therapy was recently reported to result in low numbers of local relapses in young breast cancer patients [30].…”
Section: Discussionmentioning
confidence: 99%
“…Other series also confirmed that young age is associated with increased risk for local recurrence after BCS [58][59][60] . Nevertheless, a recent population-based study from The Netherlands showed that five-year rates of developing local or regional recurrence in women < 35 years of age were only 3.5 and 3.7%, respectively 61 . These were not influenced by surgery type (BCS vs. mastectomy) and were substantially lower than reported in the past 60,62 .…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…These were not influenced by surgery type (BCS vs. mastectomy) and were substantially lower than reported in the past 60,62 . A trend for decreasing risk of locoregional breast cancer recurrence has been observed among all breast cancer patients and likely represents screening-associated stage migration, with an increasing proportion of patients diagnosed with smaller tumors as well as improvements in adjuvant therapies 61 .…”
Section: Surgical Treatmentmentioning
confidence: 99%
See 1 more Smart Citation